5(x+2)=3x-2x+6

Simple and best practice solution for 5(x+2)=3x-2x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+2)=3x-2x+6 equation:


5(x+2)=3x-2x+6

We simplify the equation to the form, which is simple to understand
5(x+2)=3x-2x+6

Reorder the terms in parentheses
+(+5x+10)=3x-2x+6

Remove unnecessary parentheses
+5x+10=+3x-2x+6

We move all terms containing x to the left and all other terms to the right.
+5x-3x+2x=+6-10

We simplify left and right side of the equation.
+4x=-4

We divide both sides of the equation by 4 to get x.
x=-1

See similar equations:

| -3w^2-6w=0 | | 5m-15m=90 | | 2+6x=4x+22 | | 3x-x+12=-30 | | 7x+83-64=92 | | 2x=4x-64 | | -a/10-8=-24 | | 3a+17=-35 | | (2x^2)+12x=22 | | -x/3+4=20 | | 4(x-3)=-72 | | 116-6x=3x+8 | | 5y+14y=133 | | 3y^2-12y-15=0 | | 3x^2-12= | | n/8-3=-11 | | -6x+10=3x+91 | | 5a-6=2(2a-3) | | 9x^2+10x+28=26 | | 4(2b+3)-9=11 | | m/4+5=14 | | 6x-14+3=4 | | 3x-4=4x+10 | | 6b+2=9-4b | | 3x(5-2x)=x-21 | | lgx=3 | | 6x+4y-5=0 | | k/9-1=10 | | -x^2-2x+1=0 | | x/2+7=11 | | x+(x+6)=60 | | 2(3x+1)-4=16 |

Equations solver categories